Developing Secure IoT Services: A Security-Oriented Review of IoT Platforms - Daniel Díaz López; Blanco Uribe, María; Tarquino Murgueitio, Daniel; Garcia Garcia, Edwin; Nespoli, Pantaleone; Gómez Mármol, Félix; Santiago Cely, Claudia Patricia (Suiza, 2018)
Undoubtedly, the adoption of the Internet of Things (IoT) paradigm has impacted on our every-day life, surrounding us with smart objects. Thus, the potentialities of this new market attracted the industry, so that many enterprises developed their own IoT platforms aiming at helping IoT services’ developers. In the multitude of possible platforms, selecting the most suitable to implement a specific service is not straightforward, especially from a security perspective. This paper analyzes some of the most prominent proposals in the IoT platforms market-place, performing an in-depth security comparison using five common criteria. These criteria are detailed in sub-criteria, so that they can be used as a baseline for the development of a secure IoT service. Leveraging the knowledge gathered from our in-depth study, both researchers and developers may select the IoT platform which best fits their needs. Additionally, an IoT service for monitoring commercial flights is implemented in two previously analyzed IoT platforms, giving an adequate detail level to represent a solid guideline for future IoT developers.

Sin lugar a dudas, la adopción del paradigma de Internet de las cosas (IoT) ha impactado en nuestra la vida cotidiana, rodeándonos de objetos inteligentes. Así, las potencialidades de este nuevo mercado atrajeron la industria, por lo que muchas empresas desarrollaron sus propias plataformas de IoT con el objetivo de ayudar a IoT desarrolladores de servicios. En la multitud de plataformas posibles, seleccionar la más adecuada para implementar un servicio específico no es sencillo, especialmente desde una perspectiva de seguridad. Este artículo analiza algunas de las propuestas más destacadas en el mercado de plataformas de IoT, realizando un análisis en profundidad comparación de seguridad utilizando cinco criterios comunes. Estos criterios se detallan en subcriterios, de modo que se pueden utilizar como base para el desarrollo de un servicio de IoT seguro. Aprovechando el conocimiento recopilados de nuestro estudio en profundidad, tanto los investigadores como los desarrolladores pueden seleccionar la plataforma de IoT que se adapta mejor a sus necesidades. Adicionalmente, se implementa un servicio de IoT para monitorear vuelos comerciales en dos plataformas de IoT previamente analizadas, dando un nivel de detalle adecuado para representar una pauta sólida para futuros desarrolladores de IoT.
Keywords: Internet de las cosas; Seguridad informática; Ciberseguridad; Internet of Things; IoT platforms; Information security; IoT security